## Teaching the Intro to Product Rule Easily

Laws of Exponents:

px * py = px+y

(px)y = pxy

p0 = 1

Product of exponent expressions with the identical base but with distinct powers:

Product of two exponent expressions having the same base and distinct powers results into the common base with the total of those powers.

px * py = px+y.

For example, 23 * 22 = (2)3+2 = 25 = 2 * 2 * 2* 2 * 2* 2 = 32 and 51× 52 = 51+2 = 53 = 5 * 5 * 5 = 125.

This product rule applies to exponents with negative bases or powers and fractional exponents.

Product of exponent expressions with distinct bases but the same powers:

px * qx = (p * q)x, here p and q are non-zero numbers.

For example, 22 * 32 = (2 ...

Show all